Self-tuning fuzzy PID controller using online method in essential oil extraction process - Mohd Yusoff, Zakiah; Muhammad, Zuraida; Zainal Abidin, Amar Faiz; Abdul Aziz, Mohd Azri; Ismail, Nurlaila; Rahiman, Mohd Hezri Fazalul (2017)
During the extraction process, the temperature plays the major effect on the quality and output yield.Numerous studies on this domain mention that excessive heat during the extraction process will degrade the quality of oil and produced poor output.Recently, researchers take efforts to fix this problem by develop intelligent control technique in order to regulate the temperature. This study proposed the self-tuning fuzzy PID (STFPID) controller using online method. The STFPID controller will regulate the steam temperature below 100OC where very little publication so far discussed on that range.The robustness of STFPID controller was test using load disturbance and set point tracking.The performance effectiveness was evaluated based on rise time, settling time, percent overshoot, and steady stare error.From the simulation result, the STFPID controller shows good performance in both transient and steady state dynamics.The STFPID controller also has the ability to track the set point change and curb the load disturbance.